BENTUK PEMBELAJARAN BIDANG SAIN DALAM MENINGKATKAN MUTU DI PERGURUAN TINGGI - Abhanda Amra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2008)
Science learning forms to improve the quality of university students’ learning are aimed are aimed at figuring out learning models which promote students’ learning ability simply and efficiently on the basis of knowledge and skills needed in learning process-self learning. Adapting current technology toward science learning has become one of the goals of learning model innovation. Furthermore, science leaning models have strength in 3 aspects: (1) problem-solving learning, (2) experience-based learning, and (3) individual and cooperation-based learning. Among some forms of learning can be applied in science learning are (a) learning model through analogy, (2) learning model through media, and (c) information technology (web)-based learning. Several components need to be well managed to ensure that such learning model innovation can be effectively applied to obtain the goals are: professional teachers, students, educational facilities, learnig process, curriculum, monitoring and evaluation.Kata Kunci: pembelajaran, sain, mutu